2017
DOI: 10.14348/molcells.2017.0002
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis MAP3K16 and Other Salt-Inducible MAP3Ks Regulate ABA Response Redundantly

Abstract: In the Arabidopsis genome, approximately 80 MAP3Ks (mitogen-activated protein kinase kinase kinases) have been identified. However, only a few of them have been characterized, and the functions of most MAP3Ks are largely unknown. In this paper, we report the function of MAP3K16 and several other MAP3Ks, MAP3K14/15/17/18, whose expression is salt-inducible. We prepared MAP3K16 overexpression (OX) lines and analyzed their phenotypes. The result showed that the transgenic plants were ABA-insensitive during seed g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…The authors also reported the in vitro phosphorylation of WRKY53 by MEKK1, but no in planta evidence has supported this result yet. Likewise, Arabidopsis MAP3K16 interacts with and phosphorylates in vitro the negative regulator of ABA response ABR1, but here as well in planta evidence is lacking (Choi et al, 2017 ). Arabidopsis MAP3K20 directly interacts with MPK18 and phosphorylates MPK18 in vitro on the TDY motif of its activation loop (Benhamman et al, 2017 ).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 95%
“…The authors also reported the in vitro phosphorylation of WRKY53 by MEKK1, but no in planta evidence has supported this result yet. Likewise, Arabidopsis MAP3K16 interacts with and phosphorylates in vitro the negative regulator of ABA response ABR1, but here as well in planta evidence is lacking (Choi et al, 2017 ). Arabidopsis MAP3K20 directly interacts with MPK18 and phosphorylates MPK18 in vitro on the TDY motif of its activation loop (Benhamman et al, 2017 ).…”
Section: Conclusion and Future Prospectsmentioning
confidence: 95%
“…Both drought stress and high salinity decrease the water availability to plant cells and also cause the accumulation of ROS such as hydrogen peroxide ( Hasegawa et al, 2000 ). As homologs of CaDIMK1, AtMAPKKK15/16/17/18 are salt-inducible MEKK genes ( Choi et al, 2017 ). In rice, OsMAPKKK63 is also induced by salt and its loss-of-function mutant shows decreased tolerance to salt stress ( Na et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…KEGG enrichment assigned the gene to plant MAPK signaling pathway. The MAPK module directly responds to ABA, or interacts with MKK3; for example, MAP3K16 is the negative regulator of ABA response (ABR1), and MAP3K17/18-MKK3-MPK1/2/7/14 responds to ABA, senescence and dormancy in Arabidopsis [ 57 , 58 ]. MKK3 contains an NTF2 domain and its primary gene structure is highly conserved during evolution [ 59 ].…”
Section: Discussionmentioning
confidence: 99%